2022
DOI: 10.1186/s12984-022-01045-z
|View full text |Cite
|
Sign up to set email alerts
|

Myoelectric interface training enables targeted reduction in abnormal muscle co-activation

Abstract: Background Abnormal patterns of muscle co-activation contribute to impaired movement after stroke. Previously, we developed a myoelectric computer interface (MyoCI) training paradigm to improve stroke-induced arm motor impairment by reducing the abnormal co-activation of arm muscle pairs. However, it is unclear to what extent the paradigm induced changes in the overall intermuscular coordination in the arm, as opposed to changing just the muscles trained with the MyoCI. This study examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…Stroke-related studies had the largest number of participants, including in total of 850 individuals, and 609 of them were patients. Seven studies recruited over 30 patients [ 43 , [86] , [87] , [88] , [89] , [90] , [91] ]. The number of patients and healthy subjects in each study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Stroke-related studies had the largest number of participants, including in total of 850 individuals, and 609 of them were patients. Seven studies recruited over 30 patients [ 43 , [86] , [87] , [88] , [89] , [90] , [91] ]. The number of patients and healthy subjects in each study is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, considering the limitation of practical applications, especially for patients, MVC is often difficult to measure. In this review, twenty-one studies reported the employment of alternative normalization methods, which were classified into five types: MVC (9.52%, percentage of the studies) [ 99 , 102 ], maximum value (MAX, 38.1%) [ 60 , 89 , 90 , 92 , 93 , 98 , 119 , 131 ], average value (AVE, 9.52%) [ 101 , 127 ], or median value (MED, 14.29%) [ 104 , 110 , 115 ] of the amplitude of the recorded EMG signals, and unit variance (UVA, 28.57%) [ 75 , 91 , 95 , 108 , 124 , 125 ].…”
Section: Resultsmentioning
confidence: 99%
“…The signi cance of the similarity score of the muscle synergies in comparison was tested by computing the similarity score of all possible pairs of a random synergy set, 1000 synergies randomly selected from the entire synergy sets identi ed in this study. The 95th percentile level of the similarity scores computed from the random synergy sets was used as a similarity threshold (Th sim = 0.78) [30,36,50,52] to determine the signi cance of a similarity score of muscle synergies.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…This suggests that muscle synergies may be formed by adaptive processes in relationship to the experiences of each individual. Long-term training can target abnormal coactivation, particularly of the most abnormally co-activating muscle pair 42 . Consequently, the relatively concentrated similarity of muscle synergies observed between the group A (Fig 8)…”
Section: The Similarity Of Muscle Synergymentioning
confidence: 99%